If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = (4x + -2)(m + 7) Reorder the terms: 5x = (-2 + 4x)(m + 7) Reorder the terms: 5x = (-2 + 4x)(7 + m) Multiply (-2 + 4x) * (7 + m) 5x = (-2(7 + m) + 4x * (7 + m)) 5x = ((7 * -2 + m * -2) + 4x * (7 + m)) 5x = ((-14 + -2m) + 4x * (7 + m)) 5x = (-14 + -2m + (7 * 4x + m * 4x)) Reorder the terms: 5x = (-14 + -2m + (4mx + 28x)) 5x = (-14 + -2m + (4mx + 28x)) 5x = (-14 + -2m + 4mx + 28x) Solving 5x = -14 + -2m + 4mx + 28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4mx' to each side of the equation. -4mx + 5x = -14 + -2m + 4mx + -4mx + 28x Combine like terms: 4mx + -4mx = 0 -4mx + 5x = -14 + -2m + 0 + 28x -4mx + 5x = -14 + -2m + 28x Add '-28x' to each side of the equation. -4mx + 5x + -28x = -14 + -2m + 28x + -28x Combine like terms: 5x + -28x = -23x -4mx + -23x = -14 + -2m + 28x + -28x Combine like terms: 28x + -28x = 0 -4mx + -23x = -14 + -2m + 0 -4mx + -23x = -14 + -2m Reorder the terms: 14 + 2m + -4mx + -23x = -14 + -2m + 14 + 2m Reorder the terms: 14 + 2m + -4mx + -23x = -14 + 14 + -2m + 2m Combine like terms: -14 + 14 = 0 14 + 2m + -4mx + -23x = 0 + -2m + 2m 14 + 2m + -4mx + -23x = -2m + 2m Combine like terms: -2m + 2m = 0 14 + 2m + -4mx + -23x = 0 The solution to this equation could not be determined.
| 4x(3x+5)= | | 5w-5w= | | 3=7x+10 | | 16x^2+4=36 | | 4.2x-3=1-x | | (x+2)(x-3)=(x-4)(x+5) | | -2(x-3)=2 | | 16K^2-36= | | 7a^2+13x-2= | | 5m=17 | | 5x^2-22=-10x | | X^2+22x+5= | | 18+x+2x=39 | | 0=2x^4-5x^2+1 | | 5t+2(1-5t)= | | 90+x-24+x=180 | | X*2-6x-7=0 | | (25b-8)-6(4b+3)=-2 | | .5x^2-3x=-9 | | (2z+7)(9-z)=0 | | 4x-(3x+6)=0 | | (8a+7)(2a^2+7a-9)= | | 11(t-5)+7t=6(3t+3)-9 | | 2B+4B-4=20 | | 2y-8=-3y-8 | | (9y^2-7y+9)-(7y^2-7y+8)= | | 49x^2-14x=-1 | | -2(5s-6)-12=-3(8s+2)-3 | | 6x+5x+4+9=7x+4+3x | | 49x^2-14=-1 | | -2(4s-3)-6=-3(9s+1)-3 | | x+xy=0xy |